Seasonal habitat use of the West-Pannonian great bustard (Otis tarda): insights from seven years of conservation practice in Central European agro-steppe habitats - Soňa Svetlíková; Péter Spakovszky; Rainhard Raab; Maximilian Raab; Adam Šupčík; Ján Škrábal; Jochen Steindl; Hannah Böing; Ladislav Naďo; Jozef Ridzoň; Rainer Raab (Journal for Nature Conservation, 2026)

Red kite (Milvus milvus) collision risk is higher at wind turbines with larger rotors and lower clearance, evidenced by GPS tracking - Jan Škrábal; Maximilian Raab; Rainhard Raab; Martin U. Grüebler; Urs G. Kormann; Patrick Scherler; Petra Sumasgutner; Susanne Åkesson; Ana Bermejo; Nayden Chakarov; Wolfgang Fiedler; Alfonso Godino; et al. (Biological Conservation, 2025)

Breeding behaviour of Central European Red Kites: parental sex-dependent differences - Marek Dostál; Jan Škrábal; Rainer Raab; Péter Spakovszky; Hynek Matušík; Ján Svetlík; Boris Maderič; Karel Makoň; Ivan Literák (Journal of Ornithology, 2025)
The breeding behaviour of raptors is determined by many characteristics, such as courtship and mating patterns, nest building, foraging, territorial defence activities, clutch incubation, and caring for the young. Here, we study the breeding behaviour of the Red Kite ( Milvus milvus ), a European native bird of prey. From a period between 2018 and 2022, we analysed data for 33 adult Red Kites (14 males and 19 females) during 70 successful breeding episodes in Austria, the Czech Republic, and Slovakia. Using satellite telemetry and in situ observations, we found differences between males and females in the size of the home range, number of nights on the nest, and maximum distances from the nest. We analysed the influence of different factors on movement activity, breeding productivity, and home range size. Females spent significantly more nights on the nest than did males, flew shorter distances from the eyrie, and occupied smaller areas. Red Kites with two or more breeding experiences arrived significantly earlier than did unexperienced Kites in their first breeding attempts. Juveniles departed from the nest sooner than did their parents. Birds with more fledged juveniles occupied smaller home ranges. Our study reveals new knowledge of substantially different breeding behaviours in male and female Central European Red Kites.

Effects of wind turbine dimensions on the collision risk of raptors: A simulation approach based on flight height distributions - Tonio Schaub; Raymond H.G. Klaassen; Caroline De Zutter; Pascal Albert; Olivier Bedotti; Jean-Luc Bourrioux; Ralph Buij; Joël Chadœuf; Celia Grande; Hubertus Illner; Jérôme Isambert; Kjell Janssens; et al. (Science of The Total Environment, 2024)

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

Iodine in plant-based dairy products is not sufficient in the UK: A market survey - Ali Alzahrani; Rainer Ebel; Gareth Norton; Andrea Raab; Joerg Feldmann (Journal of Trace Elements in Medicine and Biology, 2023)

Dispersal and philopatry in Central European Red Kites Milvus milvus - Ivan Literák; Rainer Raab; Jan Škrábal; Stanislav Vyhnal; Marek Dostál; Hynek Matušík; Karel Makoň; Boris Maderič; Péter Spakovszky (Journal of Ornithology, 2022)

Seasonal differences in migration strategies of Red Kites (Milvus milvus) wintering in Spain - Jorge García-Macía; Javier Vidal-Mateo; Javier De La Puente; Ana Bermejo; Rainer Raab; Vicente Urios (Journal of Ornithology, 2022)
Red Kite shows a great variability in its migration strategies: most individuals in north-eastern Europe are migrants, but there is also a growing number of sedentary individuals. Here, we tagged 49 Red Kites wintering in Spain with GPS/satellite transmitters between 2013 and 2020 to study the autumn and spring migration between the breeding or summering areas in Central Europe and the wintering quarters in Spain. In first place, differences between immatures and adults were found for spring migration. Adults began the spring migration towards the northeast in February–March while the immature individuals began to migrate significantly later and showing a wider date range (February-June). Adults also takes significantly less days to arrive at their destinations (12 ± 5 days) and cover more distance per day (134.2 ± 37.1 km/day) than immatures (19 ± 11 days and 98.9 ± 21.2 km/day). In second place, we also found differences between spring and autumn migration (excluding immatures). Spring migrations were clearly faster and with less stopovers days than autumn migrations. Autumn migration began between mid-October and late November and two different behaviours were observed: most birds made a quick migration direct to the wintering areas with only some days of stopovers, but others prolonged the migration with long stops along the route. These results highlight a great variation in the migratory movements of Red Kite, not only according to age but also between individuals and seasons.

Spatial and numerical responses of Red Kites Milvus milvus to the Common Vole Microtus arvalis population outbreak in central Europe - Marek Dostál; Emil Tkadlec; Rainer Raab; David Horal; Hynek Matušík; Dana Rymešová; Ivan Literák (European Journal of Wildlife Research, 2021)

Weather-influenced water-crossing behaviour of black kites (Milvus migrans) during migration - Ivan Literák; Simona Ovčiariková; Jan Škrábal; Hynek Matušík; Rainer Raab; Péter Spakovszky; Maxim Vysochin; Enikő Anna Tamás; Béla Kalocsa (Biologia, 2021)

Natal dispersal in Black Kites Milvus migrans migrans in Europe - Simona Ovčiariková; Jan Škrábal; Hynek Matušík; Karel Makoň; Jakub Mráz; Volen Arkumarev; Vladimir Dobrev; Rainer Raab; Ivan Literák (Journal of Ornithology, 2020)

Diverse natal dispersal in four sibling red kites originating from Austria, including wintering in Tunisia - Ivan Literák; Rainer Raab; Marie Petretto; Jan Škrábal; Péter Spakovszky; Jochen Steindl (Biologia, 2020)

In vitro characterisation of the anti-intravasative properties of the marine product heteronemin - Sabine Kopf; Katharina Viola; Atanas G. Atanasov; Kanokwan Jarukamjorn; Lucie Rarova; Nicole Kretschy; Mathias Teichmann; Caroline Vonach; Philipp Saiko; Benedikt Giessrigl; Nicole Huttary; Ingrid Raab; et al. (Archives of Toxicology, 2013)

Xanthohumol attenuates tumour cell-mediated breaching of the lymphendothelial barrier and prevents intravasation and metastasis - Katharina Viola; Sabine Kopf; Lucie Rarova; Kanokwan Jarukamjorn; Nicole Kretschy; Mathias Teichmann; Caroline Vonach; Atanas G. Atanasov; Benedikt Giessrigl; Nicole Huttary; Ingrid Raab; Sigurd Krieger; et al. (Archives of Toxicology, 2013)